Who does science? An analysis of high school natural sciences textbooks (PNLD 2021) (Revista Contexto & Educação, 2026)
This study aims to analyze the representation of scientists in textbooks in the field of Natural Sciences and its Technologies (NST) made available in the 2021 PNLD (National Textbook Program). It is a qualitative, documentary-type research in which two textbooks, belonging to two widely used high school collections in the Missões region of Rio Grande do Sul, were analyzed. The analysis process was guided by categories established a priori, with this study focusing on the category Who Does Science. This category seeks to examine whether science is portrayed as the work of an individual scientist or as the result of a collective effort involving multiple researchers. The findings of this investigation indicate that textbooks present varying ways of representing scientists. Some demonstrate a stronger commitment to including historical aspects through elements that help humanize the process of scientific knowledge construction. However, it is notable that, in the textbooks analyzed, science is predominantly presented as the product of individual work, underestimating the importance of collaboration among researchers and erroneously suggesting that science is an individual endeavor.
Keywords: History of Science; Science Education; Textbooks